Improving Students' Vocabulary Mastery by Using Upin and Ipin Cartoon Movie at Seventh Grade Students of SMP Angkasa Mandai - Muhammad Iqbal Maliang (Hasanuddin University, 2023)
Abstract Cartoon movie are designed not only to entertain children, but cartoons can be also used to teach and educate the children. The objectives of the study that are to find out whether “Upin and Ipin” cartoon movie can improve the students’ vocabulary and to know whether there is an increase between pre test and post test about the types of vocabulary of